2008
DOI: 10.3945/ajcn.2008.26175
|View full text |Cite
|
Sign up to set email alerts
|

Eating rate is a heritable phenotype related to weight in children

Abstract: Faster eating appears to be a heritable behavioral phenotype related to higher weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
138
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(158 citation statements)
references
References 37 publications
15
138
0
5
Order By: Relevance
“…The present study further assessed the eating rate of pre-school children by actually observing their eating behaviours under the usual food-consuming environment in kindergartens. The results showed that lunch duration was associated with childhood overweight, which was coincident with the findings of a previous study that used video-recording to observe eating behaviours (20) . The video-recording study examined associations between eating rate and BMI in 10-12-year-old children who ate standard meals at home.…”
Section: Discussionsupporting
confidence: 89%
“…The present study further assessed the eating rate of pre-school children by actually observing their eating behaviours under the usual food-consuming environment in kindergartens. The results showed that lunch duration was associated with childhood overweight, which was coincident with the findings of a previous study that used video-recording to observe eating behaviours (20) . The video-recording study examined associations between eating rate and BMI in 10-12-year-old children who ate standard meals at home.…”
Section: Discussionsupporting
confidence: 89%
“…34 The rationale for combining the CCTI and NYLS items was to broaden the content coverage of the eating behavior constructs. Specifically, these 11 items were selected in advance, based on their face content, to address the following constructs of interest: food fussiness or pickiness eating, [35][36][37] appetite and hunger, [38][39][40] and self-regulatory eating. 41,42 These constructs or traits have been suggested as being potential contributors Higher scores on reactivity to food reflect a more negative reaction to or fussiness about foods.…”
Section: Methodsmentioning
confidence: 99%
“…There are heritable components in children's preferences for fruits and meats (Breen Plomin and Wardle 2006), and specific macronutrients, chiefly dietary fat (Reed et al 1997). Appetite related traits such as food cue responsiveness and eating rate also have a genetic basis Llewellyn et al 2008). And some children are genetically less attuned to physical signals of satiation, thus are at greater risk of overeating and more likely to become obese (Faith, Carnell, and Kral 2013).…”
Section: Physiological Predispositionsmentioning
confidence: 99%